CWE study of wind flow around railways: Effects of embankment and track system on sand sedimentation. Issue 208 (January 2021) - Horvat, Marko; Bruno, Luca; Khris, Sami
Abstract: Desert railways are constantly exposed to incoming sand blown by the wind. The railway body acts as an obstacle that perturbs the wind flow and the sand drift, resulting in zones of sand sedimentation and erosion. The insight into the local flow around the railway track and resulting sedimentation patterns is a necessary prerequisite to predict and prevent sand-induced limit states.The present study generally aims at filling such a gap, by investigating the local flow and the related potential sedimentation patterns around railways. The knowledge acquired about such patterns is required in the perspective of the design of innovative on-track Receiver Sand Mitigation Measures. The study adopts a Computational Wind Engineering approach to simulate the local wind flow, to obtain the shear stress field at the ground, to derive from it sand sedimentation/erosion patterns, and to obtain bulk performance metrics. The performances of different railway substructures and track systems are discussed under different incoming wind speeds and yaw angles. The simulated sedimentation/erosion patterns qualitatively agree with the field evidences observed along desert railways. The comparative analysis shows that rails elevated by humped sleepers or slab on top of a gentle-sloped substructure perform better than other track systems. Highlights: Field observed sand sedimentation patterns around railway tracks are presented. Computational Wind Engineering approach is used to simulate the local wind flow. Several conventional and non-conventional railway geometries are tested. Sedimentation patterns are obtained numerically and compared to field observed ones. The performances of different railway geometries are comparatively discussed.